Stages of Mathematics Anxiety in Primary Pupils of Bangladesh: Investigating Influence of Leading Causative Factors (Teacher’s World: Journal of Education and Research, 2023)
The presence and impact of mathematics anxiety (MA) among school children cannot be ignored. The preliminary purpose of this study was to assess the level of MA among primary pupils in Bangladesh. Additionally, four causative factors of math anxiety - which have already been identified as dominant in global context-were also investigated in the study to explore what causes MA among this age-group in Bangladesh. The current study involved 120 students from Class 3, 4 and 5 who were randomly selected from two primary schools in Dhaka. The study also purposively involved 15 math teachers of these respondents and also 20 parents - whose children were assessed as math anxious in this study.  The findings of the study indicate that a significant number of primary pupils in each of these grades are at moderate stage of math anxiety. In addition to this, students suffering at high level of math anxiety gradually increases in higher grades. Teaching approach is identified as the key factor that causes fear of mathematics which is then followed by students’ difficulties in understanding mathematics textbook.Teacher’s World: Journal of Education and Research, Vol. 48(2), Dec 2022, p.10-26